Exploring User Experience Factors for Mobile Devices in Textual Data from Questionnaires - Damian, Adriana Lopes; Martin, Graziela; Pignatelli, Raquel (Anais do Simpósio Brasileiro de Qualidade de Software (SBQS); 2025: Anais do XXIV Simpósio Brasileiro de Qualidade de SoftwareDO - 10.5753/sbqs.2025.15025, 2025)
The evaluation of User Experience (UX) prior to product launch provides insights into end-user acceptance indicators and helps identify potential issues. Therefore, it is important to conduct studies that evaluate user group perceptions, supported by various methodological approaches. Among these, questionnaires may include questions addressing both quantitative and qualitative aspects of user perception. Textual data related to qualitative aspects can be systematically analyzed to identify UX characteristics that contribute to a broader understanding of user perception. This paper presents an experience report on the classification of UX factors based on textual data collected through questionnaires. The purpose of this practice is driven by the belief that a structured analysis of UX factors can deepen the understanding of such data. We analyzed questionnaire results from two mobile device projects involving a total of 92 users, who were the respondents of the questionnaires. For this classification, 26 practitioners analyzed the textual data reported in the questionnaires. The results indicate that UX factors can provide deeper insights into usability and user satisfaction across different components of the devices. Additionally, the practitioners considered this type of classification useful for understanding the overall quality of the projects through questionnaires.